Nanoconvergence : the unity of nanoscience, biotechnology, information technology, and cognitive science - Bainbridge, William Sims (Prentice Hall, 2007)
"Nanoconvergence is the coming unification of all significant technologies based on control of structures at the nanoscale. In Nanoconvergence, William Sims Bainbridge tours the future of science and technology in plain, nontechnical English. He successfully integrates insights from far-reaching scientific fields into a compelling human story - offering insights you can use to plan your career, seek new investment opportunities, or simply understand what's coming next."--Jacket